Research on Embedded Integration of Robot Power System and Control Module: A Disinfection Robot Control System Based on an ARM Controller - Huang, Weixi; Li, Wenwei; Xu, Yong; Liang, Jia‘nan (Innovative Applications of AI, 2025)
Currently, the power system and control module of disinfection robots have low coupling, resulting in shortcomings in energy efficiency and reliability. Therefore, this paper proposes an embedded integrated control system based on an ARM controller. First, system-level indicators such as overall weight, battery life, speed, and dosage are given, and a unified DC bus and multi-level DC/DC topology are designed. Then, a power-control integrated hardware architecture and an RTOS real-time software platform are formed to achieve coordination between motion control, power management, and disinfection execution. Furthermore, a differential motion control algorithm and a dosage constraint strategy are designed. Experimental results show that the system has high power efficiency, relatively stable temperature rise, small trajectory tracking error, speed response that meets real-time requirements, uniform disinfection coverage, and a high logarithmic kill rate under various operating conditions. Its robustness is verified after long-term operation and fault injection tests.